Evidence-based anticancer materia medica - Cho, William C.S (Evidence-based anticancer complementary and alternative medicine, 2011)
Cancer is one of the leading killers in the world and the incidence is increasing, but most cancer patients and cancer survivors suffer much from the disease and its conventional treatments? side effects. In the past, clinical data showed that some complementary and alternative medicine (CAM) possessed anticancer abilities, but some clinicians and scientists have queried about the scientific validity of CAM due to the lack of scientific evidence. There is great demand in the knowledge gap to explore the scientific and evidence-based knowledge of CAM in the anticancer field. With this aim, a book series is needed to structurally deliver the knowledge to readers. Recently there have been encouraging results from both laboratory experiments and clinical trials demonstrating the anticancer effects of herbal medicine. There is considerable interest among oncologists and cancer researchers to find anticancer agents in herbal medicine. This volume is a specialised book presenting the up-to-date scientific evidence for anticancer herbal medicine. This unique book provides an overview of the anticancer herbal medicines and remedies, as well as a detailed evidence-based evaluation of 18 common anticancer herbal medicines covering their biological and pharmacological properties, efficacies, herb-drug interactions, adverse effects, pre-clinical studies, and clinical applications. Gathering international opinion leaders? views, this volume will contribute great to the cancer, academic, and clinical community by providing evidence-based information on the anticancer efficacy of herbal medicine. Readership Oncologists, cancer researchers, pharmacologists, pharmaceutical specialists, Chinese medicine practitioners, medical educators, postgraduates and advanced undergraduates in biomedical disciplines, cancer caregivers, cancer patients.